Prevalence of myocardial viability assessed by single photon emission computed tomography in patients with chronic ischaemic left ventricular dysfunction. Issue 2 (1st August 2002) - Schinkel, A F L; Bax, J J; Sozzi, F B; Boersma, E; Valkema, R; Elhendy, A; Roelandt, J R T C; Poldermans, D
Abstract : Objective: To assess the prevalence of myocardial viability by technetium-99m (Tc-99m)-tetrofosmin/fluorine-18-fluorodeoxyglucose (FDG) single photon emission computed tomography (SPECT) in patients with ischaemic cardiomyopathy. Design: A retrospective observational study. Setting: Thoraxcenter Rotterdam (a tertiary referral centre). Patients: 104 patients with chronic coronary artery disease and severely depressed left ventricular function presenting with heart failure symptoms. Main outcome measures: Prevalence of myocardial viability as evaluated by Tc-99m-tetrofosmin/FDG SPECT imaging. Two strategies for assessing viability in dysfunctional myocardium were used: perfusion imaging alone, and the combination of perfusion and metabolic imaging. Results: On perfusion imaging alone, 56 patients (54%) had a significant amount of viable myocardium, whereas 48 patients (46%) did not. Among the 48 patients with no significant viability by perfusion imaging alone, seven additional patients (15%) had significantly viable myocardium on combined perfusion and metabolic imaging. Thus with a combination of perfusion and metabolic imaging, 63 patients (61%) had viable myocardium and 41 (39%) did not. Conclusions: On the basis of the presence of viable dysfunctional myocardium, 61% of patients with chronic coronary artery disease and depressed left ventricular ejection fraction presenting with heart failure symptoms may be considered for coronary revascularisation. The combination of perfusion and metabolic imaging identified more patients with significant viability than myocardial perfusion imaging alone.